Development of Homogeneous Carboxylation of Phenolates via Kolbe–Schmitt Reaction - Dmitry A. Merzliakov; Michael S. Alexeev; Maxim A. Topchiy; Dmitry G. Yakhvarov; Nikolai Yu. Kuznetsov; Anton L. Maximov; Irina P. Beletskaya (Molecules)
In this study, the homogeneous carboxylation of potassium, sodium, and lithium phenolates in DMSO solution at 100 °C by the Kolbe–Schmitt reaction was investigated. The impact of water, phenolate concentration, and cation nature on the yield of products and reaction selectivity was demonstrated. Based on the patterns observed, it was concluded that a complex cluster mechanism governs the carboxylation reaction in the solution. The use of a homogeneous reaction medium allowed for convenient testing of various additives to assess their impact on the reaction. Basic additives such as sodium salts of mesitol, tert-butylcalix[4]arene, sodium isopropyl, and tert-butyl cabonates were found to enhance the reaction, increasing the yield of hydroxybenzoic acids by 20% (to 61.6%). The main product in the DMSO solution was identified as 4-hydroxybenzoic acid, in contrast to the classical Kolbe–Schmitt method which typically yields 2-hydroxybenzoic (salicylic) acid. The use of 13C NMR spectroscopy enabled the observation of a “carbonate complex” in the solution for the first time, with the carbonate carbon displaying a chemical shift value of 142 ppm, an unusual finding for stable carbonates, and located between the signals of free dissolved CO2 and carboxylate derivatives.